Comparative morpho-agronomic study of Roselle genotypes based on their growth and yield traits - Akter, Keya; Islam, Md Ariful; Ali Fakir, Md Solaiman; Hoque, Md Najmol; Mehfuj, Md Anik; Yasmin, Afsana; Harine, Israt Jahan; Naher, Mst Safrun (Research in Agriculture Livestock and Fisheries, 2022)
Roselle (Hibiscus sabdariffa var. sabdariffa) is an annual subshrub, and its leaves, seeds, and especially calyces are valued for their nutritional and medicinal uses. The objectives of the study were to evaluate the best one among three morphotypes of Roselle. The morphotypes of Roselle were green plant with green calyx (WC); light red plant with light red calyx (LRC); and deep red plant with deep red calyx (DRC). The field experiment was laid out in Randomized Complete Block Design (RBCD) with three replications. Several morphological characteristics include plant height, stem base diameter, number of branches per plant, total fresh and dry biomass yield, number of capsules per plant, the weight of capsule per plant, weight of fresh calyx per plant, weight of dry calyx per plant, shelling ratio (%), etc. were evaluated. Significant differences were observed in morpho-agronomic characters in these three morphotypes. The DRC demonstrated the greatest performance across morphotypes for the number of capsules per plant (343.33), the weight of fresh capsules per plant (2227.77g), and shelling ratio (% calyx to capsule) (43.03 %). And LRC morphotype had the best performance in plant height (114.00 cm) and stem base diameter (4.30 cm). In general, the DRC morphotype outperformed the WC and LRC morphotypes. Res. Agric., Livest. Fish.9(1): 17-28, April 2022